Expression of CD73 slows down migration of skin dendritic cells, affecting the sensitization phase of contact hypersensitivity reactions in mice - Neuberger, Anna; Ring, Sabine; Silva-Vilches, Cinthia; Enk, Alexander; Mahnke, Karsten (Journal of dermatological science, 2017)
Background: Application of haptens to the skin induces release of immune stimulatory ATP into the extracellular space. This “danger” signal can be converted to immunosuppressive adenosine (ADO) by the action of the ectonucleotidases CD39 and CD73, expressed by skin and immune cells. Thus, the expression and regulation of CD73 by skin derived cells may have crucial influence on the outcome of contact hypersensitivity (CHS) reactions. Objective: To investigate the role of CD73 expression during 2,4,6-trinitrochlorobenzene (TNCB) induced CHS reactions. Methods: Wild type (wt) and CD73 deficient mice were subjected to TNCB induced CHS. In the different mouse strains the resulting ear swelling reaction was recorded along with a detailed phenotypic analysis of the skin migrating subsets of dendritic cells (DC). Results: In CD73 deficient animals the motility of DC was higher as compared to wt animals and in particular after sensitization we found increased migration of Langerin+ DC from skin to draining lymph nodes (LN). In the TNCB model this led to a stronger sensitization as indicated by increased frequency of interferon-γ producing T cells in the LN and an increased ear thickness after challenge. Conclusion: CD73 derived ADO production slows down migration of Langerin+ DC from skin to LN. This may be a crucial mechanism to avoid over boarding immune reactions against haptens.